ANALISA PENGGUNAAN PLATFORM MERDEKA MENGAJAR (PMM) DI SD NEGERI CIANDAM - Cita Suci, Amelia; Nurasiah, Iis; Khaleda Nurmeta, Irna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Platform Merdeka Mengajar (PMM) is an educational technology innovation designed to support teachers and principals in developing competencies and implementing the Merdeka Curriculum. This study aims to analyze the utilization of PMM by teachers at SD Negeri Ciandam, Cibeureum District, with a descriptive qualitative approach. The results showed that all teachers have used PMM, but only some have utilized it optimally. The Self-Training and Teaching Tools features are the most frequently used due to their relevance to developing teacher competencies and providing learning materials. The use of PMM has positive impacts, including improved knowledge, confidence, learning quality and student learning outcomes. However, some constraints were found, such as lack of training, limited network access, and technical constraints. This study recommends the provision of special training, mentoring for teachers, as well as improving network accessibility to optimize PMM utilization. The findings underscore the importance of educational technology development as part of learning transformation in the digital era.